Activating transcription factor 3 is not up-regulated in hypospadias patients in Japan - Toshiaki Takahashi; Akihiro Shimotakahara; Katsumi Miyahara; Geoffrey J Lane; Atsuyuki Yamataka (Wolters Kluwer Medknow Publications, 2013)
Background: The aetiology of hypospadias is largely uncharacterized. Some of the researchers have advocated that activating transcription factor 3 (ATF3), an oestrogen-responsive transcription factor, is up-regulated in patients with hypospadias. The purpose is to evaluate the universality of this fact; we studied the expression of ATF3 protein in prepuce tissue obtained from hypospadias and phimosis patients living in metropolitan Tokyo. Materials and Methods: Prepuce tissue was obtained from outer foreskin at the time of surgery, quickly prepared for paraffin-embedded sectioning and stained immunohistochemically for ATF3. Two researchers blindly evaluated immunoreactivity and scored it semi-quantitatively as nil = 0, weak = 1, or strong = 2, to give a final staining intensity score (SIS). Subjects were 18 hypospadias patients and 17 phimosis patients (as controls) who had surgery between January, 2009 and March, 2010. Results: All subjects lived in metropolitan Tokyo, Japan. Mean ages at surgery were 2.9 ± 1.0 and 3.9 ± 2.4 years, respectively (P > 0.05). SIS was not statistically different between hypospadias patients (1.4 ± 0.5) and controls (1.5 ± 0.5), (P > 0.05). Conclusions: Our data suggest that ATF3 is not highly associated with hypospadias in metropolitan Tokyo. Differences in ethnicity might have influenced our results.